Perceraian Orang Tua dan Karakter Remaja - Anggia Wisdani, Mimma; Widiyanti, Putri; Khoirunnisa, Tifa (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
The transition period from childhood to adulthood is called adolescence. In determining the age of adolescents, there are still many opinions that are not relevant because there are so many differences of opinion. The physical, psychological, and psychosocial aspects at this age are used as a marker of changes in the age of children towards adulthood. Recognizing self-identity in the social sphere and the world of work is one of the tasks in the adolescent stage, namely at the age of 12-20 years. So support from family, school, and the surrounding environment is a very important part. At this stage, the character of youth needs to be formed so that it can become a generation that has good qualities. Due to the process of forming character or self-identity, not far from environmental influences, the role of parents and family is very important and becomes an example or guide